Design and Build a Web-Based Medical Record Information System Using Codeigniter and Bootstrap - Zaenudin Zaenudin; Beni Iskandar Firdaus Lubis; Lalu Delsi Samsumar (Institute of Computer Science (IOCS), 2021)
The application of information systems has been widely applied today, not least in the health sector. Currently, there are many hospitals, clinics, health centers, and doctor's practices that have used information systems to facilitate management, processing and improving the security of patient data. However, not a few clinics or private health agencies still use paper media as a tool to process pa-tient data. The purpose of this research is to build a web-based information system that can be used to process patient data. This research uses literature study as a data collection method. The data taken covers the application of medical record information system records such as application de-velopment methods, system flows, and features used. To test the functionality of the system, re-searchers used the black box method in order to get precise and desired results. The result of this research is a medical record information system that was built using two frameworks, namely co-deigniter as a back-end application and bootstrap as a front-end application. With the construction of this medical record application, it is hoped that it can help health agencies that need an information system to process patient data.